Efficacy of Periodontal Endoscopy during Subgingival Debridement to Treat Periodontitis: A Systematic Review of Randomized Clinical Trials - Carlos M. Ardila; Annie Marcela Vivares-Builes (MDPI AG, 2023)
This study aims to evaluate the clinical efficacy of periodontal endoscopy (PEND) during subgingival debridement to treat periodontitis. A systematic review of randomized clinical trials (RCTs) was performed. The search strategy included four databases: PubMed, Web of Sciences, Scopus, and Scielo. The initial online exploration generated 228 reports, and 3 RCTs met the selection criteria. These RCTs described a statistically significant decrease in probing depth (PD) in the PEND group compared to controls after 6 and 12 months of follow-up. The improvement in PD was 2.5 mm for PEND and 1.8 mm for the control groups, respectively (p < 0.05). It was also described that the PEND group presented a significantly inferior proportion of PD 7 to 9 mm at 12 months (0.5%) as compared to the control group (1.84%) (p = 0.03). All RCTs noted improvements in clinical attachment level (CAL). It was described as having significant differences in bleeding on probing (BOP) in favor of PEND, with an average reduction of 43% versus 21% in the control groups. Similarly, it was also presented that they were significant differences in plaque indices in favor of PEND. PEND during subgingival debridement to treat periodontitis demonstrated efficacy in reducing PD. Improvement was also observed in CAL and BOP.